Collective Ijtihad during the Era of the Prophet ﷺ: A Model of Intellectual Unity for the Ummah - Dr. Sibghatullah; Dr. Abdul Ghani; Syed Ateequllah Agha (Journal of Quranic and Social Studies, 2025)
In the era of Prophet Muhammad (ﷺ), the concept of collective ijtihad (independent reasoning) served as a fundamental pillar for fostering intellectual unity within the Muslim community. The Prophet ﷺ established a model wherein consultation (Shura) and consensus (Ijma) were central to decision-making processes. This approach was not only instrumental in resolving disputes but also promoted unity, collaboration, and mutual respect among the companions (Sahabah). Through collective ijtihad, the Prophet ﷺ demonstrated that, despite differences in opinions, a unified and well-considered decision could be achieved, ensuring harmony and cohesion in the community. The practice of consulting the companions and encouraging collective reasoning allowed for diverse viewpoints to be heard and integrated into decisions that aligned with the teachings of the Qur'an and Sunnah. This process ensured that the community's decisions reflected the collective wisdom of its members, fostering an environment of intellectual solidarity. Importantly, this model highlighted the idea that diversity of thought within the community was not a cause for division, but rather a strength when managed through mutual consultation and agreement. In the contemporary world, this practice remains a beacon for the Muslim ummah. It provides a clear and relevant methodology for resolving modern issues within the community, where diverse opinions are prevalent. The lesson from the era of the Prophet ﷺ is that unity can be maintained through consultation, ijtihad, and consensus, even in the face of differences. This approach not only safeguards the intellectual unity of the Muslim community but also lays the foundation for its success and prosperity, both in this world and the hereafter. By adopting the principles of collective ijtihad, consultation, and consensus, Muslims can overcome divisions and work towards common goals. The example set by the Prophet ﷺ continues to be a source of guidance for modern Muslims, showing that intellectual unity, collaboration, and mutual respect are key to building a successful and harmonious community. Through these principles, Muslims can continue to thrive as a united and prosperous ummah in the modern world.